Commandments for long and safe storage of pulses - B, Kiran Gandhi; Verma, Prasoon; Kumar, Senthil; Kumar, Vaibhav; Singh, Narendra Pratap; Kumar, Krishna (Indian Farming, 2020)
In earlier days, food grains were stored at household level as per domestic requirement. With the pace of development, the culture of domestic storage has steeply fallen down. Cultural shift compounded with ‘population explosion’ has left greater scope for long-term storage of food grains including pulses. Pulses production never reached before self-sufficient to meet out the balanced dietary requirement of average sedentary man in India (40 g pulses/day/person). Therefore, import and storage of pulses has become inevitable to reach the demand and stabilization of prices. The misconceptions on ‘pulses shelf life’ and their long-term safe storage needed to answer. This article looks into the directives that can be legislated for safe and long storage of pulses.